Genetic Ablation of PDGF-Dependent Signaling Pathways Abolishes Vascular Remodeling and Experimental Pulmonary Hypertension. Issue 5 (May 2015) - ten Freyhaus, Henrik; Berghausen, Eva M.; Janssen, Wiebke; Leuchs, Maike; Zierden, Mario; Murmann, Kirsten; Klinke, Anna; Vantler, Marius; Caglayan, Evren; Kramer, Tilmann; Baldus, Stephan; Schermuly, Ralph T.; et al.
<x xml:space="preserve">Abstract</x> Objective— Despite modern therapies, pulmonary arterial hypertension (PAH) harbors a high mortality. Vascular remodeling is a hallmark of the disease. Recent clinical studies revealed that antiremodeling approaches with tyrosine–kinase inhibitors such as imatinib are effective, but its applicability is limited by significant side effects. Although imatinib has multiple targets, expression analyses support a role for platelet-derived growth factor (PDGF) in the pathobiology of the disease. However, its precise role and downstream signaling events have not been established. Approach and Results— Patients with PAH exhibit enhanced expression and phosphorylation of β PDGF receptor (βPDGFR) in remodeled pulmonary arterioles, particularly at the binding sites for phophatidyl-inositol-3-kinase and PLCγ at tyrosine residues 751 and 1021, respectively. These signaling molecules were identified as critical downstream mediators of βPDGFR-mediated proliferation and migration of pulmonary arterial smooth muscle cells. We, therefore, investigated mice expressing a mutated βPDGFR that is unable to recruit phophatidyl-inositol-3-kinase and PLCγ (βPDGFRF3/F3). PDGF-dependent Erk1/2 and Akt phosphorylation, cyclin D1 induction, and proliferation, migration, and protection against apoptosis were abolished in βPDGFRF3/F3 pulmonary arterial smooth muscle cells. On exposure to chronic hypoxia, vascular remodeling of pulmonary arteries was blunted in βPDGFRF3/F3 mice compared with wild-type littermates. These alterations led to protection from hypoxia-induced PAH and right ventricular hypertrophy. Conclusions— By means of a genetic approach, our data provide definite evidence that the activated βPDGFR is a key contributor to pulmonary vascular remodeling and PAH. Selective disruption of PDGF-dependent phophatidyl-inositol-3-kinase and PLCγ activity is sufficient to abolish these pathogenic responses in vivo, identifying these signaling events as valuable targets for antiremodeling strategies in PAH.